AB0347 Subcutaneuos (sc) methotrexate (mtx) in patients with rheumatoid arthritis (ra) as a part of "treat to target" (t2t) strategy in real practice: preliminary results of remarca study. (23rd January 2014) - Karateev, D.; Luchikhina, E.; Gridneva, G.; Muravyev, Y.; Demidova, N.; Lukina, G.; Lopareva, E.; Olyunin, Y.; Nasonov, E.
Abstract : Background: Monotherapy with MTX is the first step of RA therapy as recommended by EULAR. In accordance with the principles of T2T insufficient response to MTX requires quick switch to a combination therapy with biological agents. Objectives: We compared the short-term results of treatment of patients who responded well to MTX, and patients who switched to combination therapy after MTX failure. Methods: The REMARCA (Russian investigation of MethotrexAte and biologics in eaRly aCtive inflammatory Arthritis) ongoing investigator-initiated study includes patients with active RA who had not received SC MTX before. All patients start the treatment with SC MTX monotherapy using fast increase of the dose from 10 to 25 mg per week. The use of glucocorticoids is mainly limited to intra-articular injections. Patients are investigated monthly during first 3 months, after that therapy is revised every 3 months. The goal of treatment is to achieve clinical remission or low disease activity (LDA) in combination with good response to therapy as quickly as possible according T2T recommendations. If these results are not obtained for the next control point, we discuss to switch to combination therapy with biological agents. Results: By January 2013, 128 patients with RA were included in the study, and 53 patients (18 males, 35 females, 66% anti-CCP positive, mean duration of disease 22, 3 months, including 28 pts with early RA with duration of symptoms ≥6 months) have passed the 3 months control point, 26 patients - 6 months. After 3 months the efficacy of SC MTX have met the goal in 26 (49%) of patients. Switching to combination with biologics was required in 27 (51%) of patients: adalimumab in 16, certolizumab pegol in 3, abatacept in 7 and rituximab in 1 patient. The relations between achievement of LDA or remission according to different indices of activity and the treatment regimens are shown in the table (all differences are not statistically significant). Conclusions: Active treatment with SC MTX monotherapy can lead to the good results in the majority of patients responding to treatment (≈70% LDA, ≈39% remission). In the group of patients resistant to MTX, even a combination with a biological agent gives less response to treatment in the short term period. References: Smolen J., Landewé R., Breedveld F., et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs. Ann. Rheum. Dis., 2010, 69:964–75 Smolen J, Aletaha D, Bijlsma J, et al. Treating rheumatoid arthritis to target: recommendations of an international task force. Ann Rheum Dis, 2010, 69: 631-637 Disclosure of Interest: None Declared